1993
DOI: 10.1351/pac199365102217
|View full text |Cite
|
Sign up to set email alerts
|

Fractals in geometry of carbon black

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…In the as-received CB powder individual spherical carbon particles are loosely packed into large fractal-like aggregates [15,27] and prone to further agglomeration in dispersion. Dispersion of the native aggregates and agglomerates may be facilitated using dispersing aids.…”
Section: Conductive Composite Supportsmentioning
confidence: 99%
“…In the as-received CB powder individual spherical carbon particles are loosely packed into large fractal-like aggregates [15,27] and prone to further agglomeration in dispersion. Dispersion of the native aggregates and agglomerates may be facilitated using dispersing aids.…”
Section: Conductive Composite Supportsmentioning
confidence: 99%
“…Adsorption from solutions differs from single-gas adsorption: (i) the liquid mixture contains at least two components, each of which is adsorbed in the porous volume; (ii) the adsorption volume of AC placed in a solution is always filled with solution components, and θ = 1; (iii) the excess adsorption of solute molecules in a micropore space results in a solvent displacement from micropores. In many papers devoted to the adsorption from dilute solutions the authors applied the D−A gas/solid adsorption isotherm by replacing the adsorbate pressure with the solute concentration. Such empirical treatment had resulted in the discovery of a number of important facts.…”
Section: Introductionmentioning
confidence: 99%
“…Considerable attention to the processes of the transformation of FA in humid atmosphere was given by Lesafre [1989], Huang et al [1994], Colbeck [1995a, 1995b] and Ramachandran and Reist [1995] to the process the transformation of FA in humid atmosphere. The chemical methods were applied by Eltekova et al [1993] for determining of soot FA. The value of fractal prefactor was discussed by Nyeki and Colbeck [1995a] who showed that is close to 1.…”
Section: Phenomenology Of Atmospheric Famentioning
confidence: 99%